Preparation method and application of fluorescent Cu-MOFs nano material

By preparing fluorescent Cu-MOFs nanomaterials, the problems of low safety and poor effect of fingerprint display materials in the existing technology are solved, and the clear display of fingerprints is achieved, with simple operation, low cost and wide application range.

CN119331258APending Publication Date: 2025-01-21HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411423737.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing materials used for handprint or fingerprint display have low safety factor and poor display effect, complex operation steps and high cost, and limited scope of application.

Method used

Using the preparation method of fluorescent Cu-MOFs nanomaterials, polyvinylpyrrolidone, terephthalic acid, copper chloride dihydrate and triethylamine are mixed and stirred, followed by ultrasonic precipitation, cleaning, and freeze-drying to prepare Cu with fluorescent properties. -MOFs nanomaterials.

Benefits of technology

The fingerprint is clear and complete, the operation steps are simple, the safety factor is high, the cost is low, the scope of application is wide, and the fluorescent CU-MOFS nanomaterials have a long life fluorescent effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331258A_ABST
    Figure CN119331258A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a fluorescent Cu-MOFs nano material. The preparation method comprises the following steps: mixing and stirring polyvinylpyrrolidone, terephthalic acid, copper chloride dihydrate and triethylamine to obtain a suspension; carrying out ultrasonic treatment on the suspension, and centrifuging to obtain a precipitate; the mass ratio of polyvinylpyrrolidone to copper chloride dihydrate is (0.01-0.2): 1, the ultrasonic power is 20-80 KHZ, and within the limited range, the fluorescent Cu-MOFs nano-material is prepared, and the fluorescent Cu-MOFs nano-material has a fluorescent property and can be excited to emit a fluorescent signal, so that the fluorescent Cu-MOFs nano-material can be used for preparing the fluorescent Cu-MOFs nano-material. And the surface of the fluorescent Cu-MOFs nano material also has active sites, which is beneficial to adsorption and extraction of fingerprint components, so that the preparation process for fingerprints is simple in operation steps, high in safety coefficient, low in cost price and wide in application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials, and in particular to a preparation method and application of a fluorescent Cu-MOFs nanomaterial. Background Art

[0002] Fingerprints have become one of the key tools in biometrics because of their specificity, stability, and the characteristics of leaving traces when they touch objects. Fingerprint evidence also plays a vital and irreplaceable role and has become the most powerful means in the field of case detection and court evidence. According to the different ways of leaving fingerprints, fingerprints can be divided into three categories: obvious lines, formed lines, and latent fingerprints. Among them, latent fingerprints refer to the sweat or oil secreted by the body on the fingers. The fingerprint lines left when touching various objects inadvertently have no requirements for the object and have a high degree of randomness and necessity. Latent fingerprints are almost impossible to observe with the naked eye. They are the most important and common fingerprints at the crime scene. Latent fingerprint display is widely used in the detection of criminal cases by judicial and public security departments and other fields as well as court litigation. Nowadays, latent fingerprint display technology has become a concern for more and more scientific researchers and fingerprint workers. Researchers use a certain method or a chemical reagent with the ability to display latent fingerprints to make them special and display these latent fingerprints.

[0003] Currently, the main methods commonly used for fingerprint visualization are divided into: latent fingerprint visualization on the surface of permeable objects ① ninhydrin and DFO method ② physical developer; latent fingerprint visualization on the surface of non-permeable objects ① optical fingerprint visualization method ② "502" glue visualization method; visualization on semi-permeable objects ① fumigation method, fat staining method ② new instrumental analysis method.

[0004] The above methods are the most commonly used methods in criminal investigation and forensic identification, but these methods all have more or less shortcomings, and there are still disadvantages that are difficult to change in application or inspection. For example, the optical development method uses the principle of total reflection of light, which consumes relatively large power and cannot distinguish the authenticity of fingerprints. The ninhydrin method has certain toxicity and can cause harm to the bodies of criminal investigators. The "502" glue development method has great instability due to the temperature, humidity and dosage during use. The multi-metal deposition method has the disadvantages of high cost, cumbersome steps and poor experimental repeatability. The powder method has the problem that the particle size of most powders is at the micron level, not at the nanometer level, which may cover the ridge lines of the fingerprint and cause some erroneous information in biometric identification.

[0005] Therefore, how to effectively improve the appearance of latent fingerprints and simplify the preparation process in actual application, with higher safety factor, lower cost and wider application range, is an urgent problem to be solved by fingerprint workers and related departments. Summary of the invention

[0006] The main purpose of the present invention is to provide a preparation method of a fluorescent Cu-MOFs nanomaterial and its application, aiming to solve the problem of low safety factor and poor display effect of the materials currently used for handprint or fingerprint display.

[0007] To achieve the above object, the present invention provides a method for preparing fluorescent Cu-MOFs nanomaterials, comprising the following steps:

[0008] Mix polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine and stir to obtain a suspension;

[0009] The suspension is subjected to ultrasonication and centrifugation to obtain a precipitate;

[0010] The precipitate is washed, frozen and dried to obtain fluorescent Cu-MOFs nanomaterials, wherein the mass ratio of the polyvinyl pyrrolidone to the cupric chloride dihydrate is (0.01-0.2): 1. The power of ultrasound is 20-80KHZ.

[0011] In some embodiments, in the step of “mixing and stirring polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension”:

[0012] The cupric chloride dihydrate is cupric chloride dihydrate, and the molar ratio of the cupric chloride dihydrate to the terephthalic acid is (1-2):1.

[0013] In some embodiments, in the step of “mixing and stirring polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension”:

[0014] The stirring speed is 400-600 rpm / min; and / or,

[0015] The stirring time is 10 to 30 minutes.

[0016] In some embodiments, in the step of "sonicating and centrifuging the suspension to obtain a precipitate":

[0017] The power of ultrasound is 10 to 40 KHZ; and / or,

[0018] The ultrasound time is 0.5 to 6 hours.

[0019] In some embodiments, the step of "mixing polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension" comprises the following steps:

[0020] Dissolving polyvinyl pyrrolidone in NN-dimethylformamide to obtain a mixture;

[0021] The mixture is stirred with terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension.

[0022] In some embodiments, the step of "sonicating and centrifuging the suspension to obtain a precipitate" comprises the following steps:

[0023] The suspension is sonicated and centrifuged under light-proof conditions to obtain a precipitate.

[0024] In some embodiments, in the step of "washing, freezing, and drying the precipitate to obtain fluorescent Cu-MOFs nanomaterials":

[0025] The cleaning solvent is ethanol.

[0026] The present application provides a fluorescent Cu-MOFs nanomaterial, wherein the fluorescent Cu-MOFs nanomaterial is prepared by the method for preparing the fluorescent Cu-MOFs nanomaterial as described in any one of the above items.

[0027] The present application also provides a fingerprint developer, which includes the fluorescent Cu-MOFs nanomaterial as described above.

[0028] The preparation method of the fluorescent Cu-MOFs nanomaterial provided by the present invention adopts polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to act together, and the mass ratio of the polyvinyl pyrrolidone to the cupric chloride dihydrate needs to be limited to (0.01-0.2): 1. The power of ultrasound is 20-80KHZ. Within this range, Cu-terephthalic acid can be dispersed in PVP. Within this condition range, the fluorescence effect is better and the life span is longer. The fluorescent Cu-MOFs nanomaterial prepared in this way has a fluorescent property and can be excited to emit a fluorescent signal, which is helpful for the appearance and observation of fingerprints. The fluorescent Cu-MOFs nanomaterial also has an active site on the surface, which can interact with the components in the fingerprint residue, is conducive to the adsorption and extraction of fingerprint components, and can be used for the appearance of fingerprints, and the fingerprint lines are clear and complete. The preparation process has simple operation steps, a higher safety factor, low cost and a wider range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the XRD characterization results of the fluorescent Cu-MOFs nanomaterial according to one embodiment of the present application.

[0030] Figure 2 This is a diagram showing the fingerprint display effect of the fluorescent Cu-MOFs nanomaterial according to one embodiment of the present application under light irradiation in different wavelength bands.

[0031] Figure 3This is a fingerprint display effect diagram of the fluorescent Cu-MOFs nanomaterial prepared at different PVP addition amounts according to one embodiment of the present application.

[0032] Figure 4 This is a diagram showing the fingerprint display effect of the fluorescent Cu-MOFs nanomaterial prepared in one embodiment of the present application at different time lengths. DETAILED DESCRIPTION

[0033] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.

[0034] Currently, the main methods commonly used for fingerprint visualization are divided into: latent fingerprint visualization on the surface of permeable objects ① ninhydrin and DFO method ② physical developer; latent fingerprint visualization on the surface of non-permeable objects ① optical fingerprint visualization method ② "502" glue visualization method; visualization on semi-permeable objects ① fumigation method, fat staining method ② new instrumental analysis method.

[0035] The above methods are the most commonly used methods in criminal investigation and forensic identification, but these methods all have more or less shortcomings, and there are still disadvantages that are difficult to change in application or inspection. For example, the optical development method uses the principle of total reflection of light, which consumes relatively large power and cannot distinguish the authenticity of fingerprints. The ninhydrin method has certain toxicity and can cause harm to the bodies of criminal investigators. The "502" glue development method has great instability due to the temperature, humidity and dosage during use. The multi-metal deposition method has the disadvantages of high cost, cumbersome steps and poor experimental repeatability. The powder method has the problem that the particle size of most powders is at the micron level, not at the nanometer level, which may cover the ridge lines of the fingerprint and cause some erroneous information in biometric identification.

[0036] In view of this, the present invention proposes a method for preparing fluorescent Cu-MOFs nanomaterials, comprising the following steps:

[0037] Mix polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine and stir to obtain a suspension;

[0038] The suspension is subjected to ultrasonication and centrifugation to obtain a precipitate;

[0039] The precipitate is washed, frozen and dried to obtain fluorescent Cu-MOFs nanomaterials, wherein the concentration ratio of the polyvinyl pyrrolidone to the cupric chloride dihydrate is (0.01-0.2): 1. The power of ultrasound is 20-80KHZ.

[0040] The fluorescent Cu-MOFs nanomaterial provided by the present invention is Figure 1 The XRD characterization results show that the film is composed of Cu-MOFs material, and the materials such as polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine are used together, and the mass ratio of the polyvinyl pyrrolidone to the cupric chloride dihydrate needs to be limited to (0.01-0.2): 1. The power of ultrasound is 20-80KHZ, so that fluorescent Cu-MOFs nanomaterials are prepared. The fluorescent Cu-MOFs nanomaterials have fluorescent properties and can be excited to emit fluorescent signals, which are helpful for the visualization and observation of fingerprints. The surface of the fluorescent Cu-MOFs nanomaterials also has active sites, which can interact with the components in the fingerprint residues, which is conducive to the adsorption and extraction of fingerprint components, so that it can be used for the visualization of fingerprints, and the fingerprint lines are clear and complete. The preparation process has simple operation steps, a higher safety factor, low cost and a wider range of applications.

[0041] It should be noted that polyvinylpyrrolidone (PVP): PVP is a high molecular polymer with good solubility and dissolvability. It can be used as a suspending agent to help disperse other ingredients (such as terephthalic acid and cupric chloride dihydrate) in the solvent, which is conducive to forming a uniform suspension; triethylamine is an alkaline solvent and may act as a neutralizer in the reaction, helping to adjust the pH of the reaction system and promote the formation of fluorescent Cu-MOFs nanomaterials.

[0042] In any embodiment of the present invention, in the step of "mixing polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension": the cupric chloride dihydrate is cupric chloride dihydrate, and the mass ratio of the polyvinyl pyrrolidone to the cupric chloride dihydrate is (0.01-0.2):1; within this ratio range, the polyvinyl pyrrolidone and the cupric chloride dihydrate react more fully, and too high or too low a polyvinyl pyrrolidone is not conducive to the formation of a Cu-terephthalic acid structure, and the fluorescence effect deteriorates. Preferably, the mass ratio of the polyvinyl pyrrolidone to the cupric chloride dihydrate can be 0.01:1, 0.05:1, 0.1:1, 0.15:1 or 0.2:1 for better reaction effect.

[0043] It should be noted that terephthalic acid is an organic acid and can be used as one of the precursors of fluorescent Cu-MOFs nanomaterials. Terephthalic acid reacts with cupric chloride dihydrate in the reaction to generate the basic skeleton of fluorescent Cu-MOFs nanomaterials. Cupric chloride dihydrate undergoes a coordination reaction with terephthalic acid in the reaction to generate the structure of fluorescent Cu-MOFs nanomaterials.

[0044] In any embodiment of the present invention, in the step of "mixing polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension": the cupric chloride dihydrate is cupric chloride dihydrate, and the molar ratio of the cupric chloride dihydrate to the terephthalic acid is (1-2):1. Within this molar ratio range, the reaction effect is better. Preferably, the molar ratio of the cupric chloride dihydrate to the terephthalic acid can be 1:1, 1.5:1, or 2:1.

[0045] In any embodiment of the present invention, in the step of "mixing polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension", the stirring speed is 400-600 rpm / min. Within this stirring speed range, the mixing can be more uniform, the reaction can be carried out more fully, and the reaction efficiency can be improved. The stirring speed can be 400 rpm / min, 450 rpm / min, 500 rpm / min, 550 rpm / min, 600 rpm / min.

[0046] In any embodiment of the present invention, in the step of "mixing polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine and stirring to obtain a suspension": the stirring time is 10 to 30 minutes. Within this range, the stirring can be more uniform, and the stirring time can be 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes.

[0047] In any embodiment of the present invention, in the step of "ultrasonicating the suspension and centrifuging to obtain a precipitate": the ultrasonic time is 0.5 to 6 hours. Within this ultrasonic range, the ultrasonic effect is better. The ultrasonic time can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.

[0048] In any embodiment of the present invention, the step of "mixing polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension" comprises the following steps:

[0049] Dissolving polyvinyl pyrrolidone in NN-dimethylformamide to obtain a mixture;

[0050] The mixture is stirred with terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension.

[0051] In any embodiment of the present invention, the step of "ultrasonicating and centrifuging the suspension to obtain a precipitate" includes the following steps: ultrasonicating and centrifuging the suspension under light-proof conditions to obtain a precipitate, wherein the light-proof conditions can prevent the reaction from excessive complexation reaction leading to agglomeration.

[0052] In any embodiment of the present invention, in the step of "washing, freezing and drying the precipitate to obtain fluorescent Cu-MOFs nanomaterials": the washing solvent is ethanol, which makes the washing more thorough and does not leave other impurities.

[0053] The present application provides a fluorescent Cu-MOFs nanomaterial, which is prepared by the preparation method of the fluorescent Cu-MOFs nanomaterial as described in any of the above items. Therefore, it also has the beneficial effects of the above fluorescent Cu-MOFs nanomaterials, which will not be described one by one here.

[0054] The present application also provides a fingerprint developer, which includes the fluorescent Cu-MOFs nanomaterial as described above and can be used in criminal investigation or other industries.

[0055] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0056] Example 1

[0057] A method for preparing a fluorescent Cu-MOFs nanomaterial comprises the following steps:

[0058] Dissolve 0.10 g of polyvinyl pyrrolidone (PVP) in 32 mL of NN-dimethylformamide solvent to obtain a mixed solution. Add 0.75 mmol of terephthalic acid to the obtained mixed solution and stir continuously for 10 min at 25°C, add 0.75 mmol of cupric chloride dihydrate, and then quickly inject 0.8 mL of triethylamine (TEA) into the above solution with a pipette, stir evenly for 10 min at a stirring speed of 500 rpm / min to form a uniform suspension;

[0059] The suspension was transferred to a dark environment and continuously sonicated at 40 KHZ for 6 h. After the sonication, the resulting solution was centrifuged to obtain a light blue precipitate.

[0060] The precipitate was washed three times by centrifugation with ethanol and ultrapure water respectively, the washed precipitate was placed in a special container and pre-frozen with liquid nitrogen, and the preliminarily frozen sample was further placed in a freeze dryer for freeze drying for 24 hours. After freeze drying, the sample was taken out and ground to obtain powdered fluorescent Cu-MOFs nanomaterials.

[0061] In the steps of the preparation method of the fluorescent Cu-MOFs nanomaterials in Examples 2 to 7, except for the addition amount of PVP and the ultrasonic frequency, the other raw materials and preparation methods are the same as those in Example 1, as shown in Table 1 for details.

[0062] Comparative Example 1

[0063] A method for preparing a fluorescent Cu-MOFs nanomaterial is the same as Example 1 except that the amount of PVP added is replaced with a range value.

[0064] In Comparative Examples 2 to 4, the amount of PVP added and the ultrasonic power were replaced with other values, and the rest were the same as in Example 1.

[0065] Specifically, the amount of PVP added and the ultrasonic frequency of each embodiment and comparative example are shown in Table 1:

[0066] Table 1

[0067]

[0068] Performance Testing

[0069] The fluorescent Cu-MOFs nanomaterials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to fluorescence intensity analysis. The analysis results are shown in Table 2:

[0070] Table 2:

[0071] Project Name Fluorescence intensity (%) Texture clarity Example 1 100% Clear and complete texture Example 2 92% Clear and complete texture Example 3 98% Clear and complete texture Example 4 90% Clear and complete texture Example 5 95% Clear and complete texture Comparative Example 1 90% The texture is relatively clear, but not complete. Comparative Example 2 80% The texture is not clear and incomplete Comparative Example 3 40% The texture is not clear, relatively complete Comparative Example 4 60% The texture is relatively clear, but not complete.

[0072] The fluorescent Cu-MOFs nanomaterials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were used to brush fingerprints. The above materials were dipped into a brush and swept on the fingerprints. From the results in Table 2, it can be seen that Examples 1 to 4 limit the mass ratio range of the polyvinyl pyrrolidone to the cupric chloride dihydrate and the ultrasonic frequency, so that clear and complete fingerprint patterns can be obtained. On the contrary, outside this range, the patterns are either incomplete or unclear, which is due to the weak fluorescence effect.

[0073] Application test case

[0074] The operation steps include: first, pressing the fingerprint on the object, then using a feather brush to dip the fluorescent Cu-MOFs nanomaterial powder prepared in Example 1 and lightly brushing it on the object, and irradiating it with ultraviolet light. The above powder was tested for fluorescence intensity, multi-band light display, different objects, and storage time when the latent fingerprint was revealed, and the results were as follows:

[0075] (1) Multi-band light display:

[0076] The fluorescent Cu-MOFs nanomaterial powder prepared in Example 1 was placed on the same guest aluminum sheet and irradiated with four different wavelengths of light: 405 nm, 445 nm, 532 nm and white light. Figure 2 a, b, c and d in the figure are observed through a filter. Figure 2 The d in the figure is white light, and the observation results are as follows Figure 2 As shown, from Figure 2 It can be seen that when the wavelength is 405nm through the filter, the general fluorescence effect is poor and the fingerprint lines are not clear; when the wavelength is 445nm, the general fluorescence intensity is high, the fingerprint is clearly visible, and the effect is the best; when the wavelength is 532nm, the fluorescence effect is poor and the fingerprint lines are not clear. Therefore, the fingerprint with the best fluorescence effect can be obtained under the light of wavelength 445nm.

[0077] (2) Fluorescence intensity:

[0078] The fluorescent Cu-MOFs nanomaterials prepared in Examples 1 to 3 were irradiated with ultraviolet light of the same wavelength of 445 nm on the non-permeable guest aluminum sheet. Example 1 corresponds to Figure 3 c in Example 2 corresponds to Figure 3 a in Example 3 corresponds to Figure 3 b in the example 5 corresponds to d, and e corresponds to the result of Example 1. Figure 3 As shown, when the amount of PVP increases to 0.10g, the fingerprint has high fluorescence intensity, clear lines, uniform brightness, and no bottom blurring, and the fluorescence display effect is excellent.

[0079] (3) Storage time:

[0080] The fluorescent Cu-MOFs nanomaterial powder prepared in Example 1 was irradiated with ultraviolet light of the same wavelength of 445 nm on the non-permeable guest aluminum sheet. The results are as follows Figure 4 As shown, from Figure 4 It can be seen that the fingerprint fluorescence effects after 1 day, 14 days, 1 month, 2 months, and 3 months of retention time correspond to Figure 4 There is almost no difference in the fluorescence appearance of fingerprints among a, b, c, d and e, and they still show good fluorescence intensity.

[0081] Therefore, it can be concluded that: (1) the powdered fluorescent Cu-MOFs nanomaterial powder is prepared by the coprecipitation method, and the concentration of the raw materials and other components is controlled by adjusting the content of the solvent PVP, so as to achieve orderly regulation of the particle size of the fluorescent metal organic framework material, achieve the purpose of enhancing the fluorescence effect, and realize the latent fingerprint visualization. Compared with traditional fingerprint chemical visualization methods such as cyanoacrylate fuming method, silver nitrate method, ninhydrin method and small particle reagent method, the fluorescent Cu-MOFs nanomaterial powder prepared by the present invention is simpler to operate and has low toxicity to the human body during use, has a high visualization contrast, and can effectively meet the identification of latent fingerprints at the crime scene.

[0082] (2) The quantum size effect of fluorescent nanomaterials gives them unique optical properties such as photoluminescence. They not only have the advantages of small size, good display effect, high color contrast, good chemical and light stability, and convenient surface modification, but also the fluorescent Cu-MOFs nanomaterials prepared by the present invention have excellent Fenton performance and large surface area, which have a good effect in fingerprint display.

[0083] (3) In actual use, the best fluorescence effect of fingerprints can be obtained under light with a wavelength of 445nm.

[0084] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A method for preparing fluorescent Cu-MOFs nanomaterials, characterized in that: The following steps are involved: Mix polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine and stir to obtain a suspension; The suspension is subjected to ultrasonication and centrifugation to obtain a precipitate; The precipitate is washed, frozen, and dried to obtain fluorescent Cu-MOFs nanomaterials; Wherein, the mass ratio of the polyvinyl pyrrolidone to the cupric chloride dihydrate is (0.05-0.15):

1. The power of the ultrasound is 20-80KHZ.

2. The method for preparing the fluorescent Cu-MOFs nanomaterial according to claim 1, characterized in that: In the step of "mixing and stirring polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension": The molar ratio of the cupric chloride dihydrate to the terephthalic acid is (1-2):

1.

3. The method for preparing the fluorescent Cu-MOFs nanomaterial according to claim 1, characterized in that: In the step of "mixing and stirring polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension": The stirring speed is 400-600 rpm / min; and / or, The stirring time is 10 to 30 minutes.

4. The method for preparing the fluorescent Cu-MOFs nanomaterial according to claim 1, characterized in that: In the step of "subjecting the suspension to ultrasound and centrifugation to obtain a precipitate": The power of ultrasound is 10 to 40 KHZ; and / or, The ultrasound time is 0.5 to 6 hours.

5. The method for preparing the fluorescent Cu-MOFs nanomaterial according to claim 1, characterized in that: The step of "mixing polyvinyl pyrrolidone, terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension" comprises the following steps: Dissolving polyvinyl pyrrolidone in NN-dimethylformamide to obtain a mixture; The mixture is stirred with terephthalic acid, cupric chloride dihydrate and triethylamine to obtain a suspension.

6. The method for preparing the fluorescent Cu-MOFs nanomaterial according to claim 1, characterized in that: The step of "sonicating and centrifuging the suspension to obtain a precipitate" comprises the following steps: The suspension is sonicated and centrifuged under light-proof conditions to obtain a precipitate.

7. The method for preparing the fluorescent Cu-MOFs nanomaterial according to claim 1, characterized in that: In the step of "washing, freezing and drying the precipitate to obtain fluorescent Cu-MOFs nanomaterials": The cleaning solvent is ethanol.

8. A fluorescent Cu-MOFs nanomaterial, characterized in that: The fluorescent Cu-MOFs nanomaterial is prepared by the method for preparing the fluorescent Cu-MOFs nanomaterial according to any one of claims 1 to 7.

9. A fingerprint developer, characterized in that: The fingerprint developer comprises the fluorescent Cu-MOFs nanomaterial as claimed in claim 8.